The effect of practice on performance in cloze and dictation tests to grade six pupils - Ordona, Amelia Fangon 1948- (1974)
This study determined the effect of regular practice on performance in close and dictation tests of grade six pupils at the Agoo East Central School. The pupils were divided into three groups, namely: Controlled Group, Experimental Group I and Experimental Group II to determine the effect of the treatment given to the experimental groups.
Thesis (M.Ed.)--University of the Philippines.
Keywords: Dictation (Education method).; English language -- Study and teaching